NCOG-01. CLINICAL DETERMINANTS IMPACTING OVERALL SURVIVAL OF PATIENTS WITH OPERABLE BRAIN METASTASES FROM NON-SMALL CELL LUNG CANCER. (14th November 2022) - Piffko, Andras; Asey, Benedikt; Dührsen, Lasse; Ristow, Inka; Salamon, Johannes; Wikman, Harriet; Maire, Cecile; Lamszus, Katrin; Westphal, Manfred; Sauvigny, Thomas; Mohme, Malte
Abstract: The incidence of brain metastases (BM) in non-small cell lung cancer (NSCLC) patients is continuously increasing. The recent improvements of systemic treatment in NSCLC necessitate continuous updates on prognostic subgroups and factors determining overall survival. In order to improve clinical decision-making, we investigated the clinical determinants affecting survival in patients with resectable NSCLC BM. A retrospective analysis was conducted of NSCLC patients with surgically resectable BM treated in our institution between 01/2015 and 12/2020. Relevant clinical factors affecting survival identified by univariate analysis where included in a multivariate logistic regression model. Overall, 264 patients were identified, with a mean age of 62.39 ± 9.98 years at initial diagnosis of NSCLC BM and overall survival (OS) of 23.22 ± 1.71 months. Factors that significantly affected overall survival from time of primary tumor diagnosis included the systemic metastatic load (mean: 45.9 ± 9.7 vs. 58.9 ± 9.4 months, p = 0.021) as well as a number of BM < 2 (mean: 25.5 ± 4.4 vs. 57.4 ± 7.8 months, p = 0.014). When adjusted for survival time after neurosurgical intervention, a significant survival benefit was found in patients < 60 years (32.5 ± 4.3 vs. 28.5 ± 5.2 months, p = 0.036) and patients without any concurrent systemic metastases at time of NSCLC BM diagnosis (mean 32.4 vs. 34.1, p = 0.032). Our data shows that the number of BM (singular/solitary), gender and age, but not localization (infra-/supratentorial), mass-edema index or time to BM occurrence impact overall survival in NSCLC BM patients.Additionally, our study shows that patients in prognostically favorable clinical subgroups have an overall survival, which differs significantly from current statements in literature. The described clinically relevant factors may improve the understanding of the risks and the course of this disease and aid future clinical decision making in tumor boards.